CHEMICAL COMPOSITION OF ESSENTIAL OIL (Schinus terebinthifolius Raddi) LEAVES - Yuliasri Jamal; Andria Agusta (Indonesian Journal of Pharmacy, 2001)
Schinus terebinthifolius Raddi is known to have medicinal benefit to cure various deseases. This experiment was conducted to analyse the chemical components of the essential oil of S. terebinthifolius Raddi, because the medicinal effects is strongly related to the chemical components. Chemical components analyses of the essential oil from Schinus terebinthifolius Raddi. was conducted using the combination method of Gas Chromatography and Mass Spectrometry (GCMS). Chromatograms represented 47 components in the essential oil of S. terebinthifolium leaves with 17 major components (> 1% content). They were 3-carene, -pinene, -pinene, -phellandrene (type 1), -phellandrene (type 2), D-limonene, sabinene, p-simene, -simene, -elemene, isocaryophillene, -cubebene, 4aR-(4a,7,8a)-decahydro-4a-methyl-1-methyilene-7-(1-methylethenyl) naphtalena (type 1), 4aR-(4a,7,8a)-decahydro-4a-methyl-1-methylene-7-(1-methylethenyl) naphtalena (type 2), (1,4a,8a)-1,2,4a,5,6,8a)-hexahydro-4,7-dimethyl-1-(1-methylethyl)-naphtalene, -cadinene and 1ar-(1a,4a,7,7a, 7b) -decahydro-1,1,7-trimethyl-4-methylene-1H-sicloprope azulen-7-ol. The major components were dominated mostly by monoterpene (68.63%).Key words: Schinus terebinthifolius Raddi, essential oil, chemical components